2023
DOI: 10.18502/ijm.v15i4.13503
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial etiology, antimicrobial resistance and factors associated with community acquired pneumonia among adult hospitalized patients in Southwest Ethiopia

Abdulhakim Mussema,
Getenet Beyene,
Esayas Kebede Gudina
et al.

Abstract: Background and Objectives: Antibiotic resistance is a significant problem that restricts the options for treating bacterial pneumonia. This research aimed to determine the bacterial causes of pneumonia and antibiotic resistance among hospitalized patients in southwest Ethiopia. Materials and Methods: We collected and analyzed 150 sputum samples from individuals with community-acquired pneu- monia from April 1st  to October 30th, 2019. Standard bacteriological procedures were used to identify the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
2
Order By: Relevance
“…In the present study, bacterial isolates were identified in 31.7% of the CAP patients, which is lower than the findings reported elsewhere in Ethiopia: Dessie town, Northeastern Ethiopia, 46.3% [ 26 ]; Gondar, Northwestern Ethiopia, 39.4% [ 27 ]; and Jimma town, Southwestern Ethiopia, 50.0% [ 28 ]. One possible reason for the lower level of bacterial isolates compared to the previous studies conducted in Ethiopia may be attributed to the widespread usage of antibiotics before presentation to the hospital, as 16.3% of the participants in this study had a history of prior antibiotic intake.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In the present study, bacterial isolates were identified in 31.7% of the CAP patients, which is lower than the findings reported elsewhere in Ethiopia: Dessie town, Northeastern Ethiopia, 46.3% [ 26 ]; Gondar, Northwestern Ethiopia, 39.4% [ 27 ]; and Jimma town, Southwestern Ethiopia, 50.0% [ 28 ]. One possible reason for the lower level of bacterial isolates compared to the previous studies conducted in Ethiopia may be attributed to the widespread usage of antibiotics before presentation to the hospital, as 16.3% of the participants in this study had a history of prior antibiotic intake.…”
Section: Discussioncontrasting
confidence: 87%
“…This finding is consistent with studies conducted in Uganda, where Moraxella species were found to be more prevalent [ 34 ] and retrospective observational cohort study conducted in Vienna, Austria [ 35 ], where S. aureus was the predominant isolate. However, the findings of this study was in variation with the findings conducted in Jimma town, Southwestern Ethiopia [ 28 ] where K. pneumonia and P. aeruginosa were the most frequent isolates followed by other species. The predominant M. catarrhalis in this finding showed the significant emergency of this pathogen as an etiology of pneumonia in recent years [ 36 ].…”
Section: Discussioncontrasting
confidence: 56%